Comparison of the frequency and status of coronary artery involvement in coronary angiography of opioid addicted and non-addicted individuals admitted in the cardiology ward of Imam Reza Hospital during 6 months - Alireza Abdollahi Moghaddam; vahideh mohammadzadeh; Bita Dadpour (Asia Pacific Journal of Medical Toxicology, 2021)
Introduction: Opium abuse has become a major and growing problem in most countries of the world, including Iran. The Central Nervous System (CNS) is the most affected system by opium, although the cardiovascular and respiratory systems can be affected too. The aim of this study was to compare coronary angiographic data in patients admitted with and without opioid addiction in Imam Reza (p) Hospital for six months (October 2017 to March 2018).Methods: The following cross-sectional study, patients with stable ischemic heart disease who were admitted to Imam Reza (p) Hospital for coronary angiography were studied. Risk factors for cardiovascular disease such as age, body mass index (BMI), diabetes mellitus, hyperlipidemia, hypertension, past evidence of heart problems (CVD), physical inactivity, history of heart disease in first-degree relatives and past or present cigarette smoking. Information on the history of opioid addiction was also collected for the above individuals. Coronary angiographic findings were recorded for each patient and the results were compared. Group 1 consisted of cases with minimal stenosis or without stenosis. Group 2 consisted cases with equal or more than 70% stenosis in single, 2 or 3 vessels or more than 50% stenosis in left main. Finally, the two groups of addicted and non-addicted people were compared in terms of angiographic findings.Results: No significant difference was observed among the two groups In terms of BMI, diabetes mellitus, hyperlipidemia, hypertension, past evidence of heart problems (CVD), physical inactivity, history of heart disease in first-degree relatives and smoking. Additionally, No significant difference in the incidence of angiographic problems was found between opioid addicts and non-addict cases.Conclusion: The adverse effects of opioid addiction on different organs such as the cardiovascular system is a challenging subject In term of probable protective effects of these compounds against cardiac problems or their inductive effects on heart problems The current study found no significant relationship between opioid addiction and coronary angiographic findings. Further investigation with larger sample size is recommended.